The 2019 H. Paul Douglass Lecture: I Can’t Keep Quiet: Engaging with Scholarly Research on Religion - Bruce, Tricia Colleen (Review of religious research, 2020)
Methodologies used by social scientists grant access to quiet worlds and otherwise hidden truths. Social scientists are akin to strangers, trusted with secrets. The 2019 H. Paul Douglass Lecture proposes that scholars who engage with research on religion ought to listen quietly, but not keep quiet. We can transform the quiet to which we are privy into the collective. I illustrate the imperative to speak research out loud using the case example of the National Abortion Attitudes Study. Personal knowledge becomes collective revelation and, sometimes, social change.